2022
DOI: 10.1590/fst.08022
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities and chemical profile of Hericium erinaceus mycelium cultivated on mixed red and white jasmine rice

Abstract: Functional foods have received considerable attention due to their numerous health benefits. Lion's mane mushroom (Hericium erinaceus) is a functional food source that contains bioactive compounds of medicinal importance. The main aim of this study was to explore antimicrobial and anticancer activities and identify bioactive compounds of H. erinaceus mycelia cultivated on mixed red and white jasmine rice (HMR) with the aid of solid-state fermentation (SSF). The HMR extract and its fractions were analyzed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Tannin plays a major role in antimicrobial activity by inactivating membrane-bound enzymes, transport proteins and cell-to-cell adhesions [ 58 ]. Fatty acid derivatives were also identified in the GC-MS analysis, which may contribute to the antimicrobial activity of solvent extracts [ 78 ]. Talreja et al [ 79 ] investigated the antibacterial potential of Ulva lactuca , and methanolic extract showed strong activity against S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…Tannin plays a major role in antimicrobial activity by inactivating membrane-bound enzymes, transport proteins and cell-to-cell adhesions [ 58 ]. Fatty acid derivatives were also identified in the GC-MS analysis, which may contribute to the antimicrobial activity of solvent extracts [ 78 ]. Talreja et al [ 79 ] investigated the antibacterial potential of Ulva lactuca , and methanolic extract showed strong activity against S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…H. erinaceus mycelia were cultivated (substrate composed of corn cob [15 g]), rice bran [20 g]), sawdust [65 g]), moisture 50%–60% and pH 3.6–6.6) and delivered by our co-authors in the Department of Microbiology, Faculty of Science, Kasetsart University; analysis of erinacine content was performed with high performance liquid chromatography mass spectrometry (HPLC-MS) by our co-author in the Department of Chemistry, Faculty of Science, Kasetsart University. All details were described in our previous report ( Darmasiwi et al . 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…At present, rice quality detection and evaluation methods have been frequently reported based on flavor information (Verma & Srivastav, 2020). At the same time, relevant odor analysis technologies, including solid-phase micro-extraction technology combined with gas chromatography-mass spectrometry (Darmasiwi et al, 2022), gas chromatography-ion mobility spectrometry (GC-IMS) and electric nose technology (Cui et al, 2018) have also been applied in the fields of key odor component screening of fragrant rice (Zhao et al, 2020b), rice variety distinction (Sung et al, 2014), microbial toxin infection detection (Gu et al, 2020), rice geographical origin identification (Lim et al, 2018) and adulteration analysis (Fan & Yang, 2022;Timsorn et al, 2017). In addition, previous studies have also demonstrated that partial VOCs (like aldehydes, ketones, and furans) would change in high temperature storage, which was an important reason for decline of rice quality during storage (Shi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%